2012
DOI: 10.1080/17470218.2011.636823
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive and exteroceptive attention have opposite effects on subsequent somatosensory perceptual decision making

Abstract: Evidence suggests that interoceptive and exteroceptive attention might have different perceptual effects. However, the effects of these different types of body-focused attention have never been directly compared. The current research investigated how interoceptive and exteroceptive attention affect subsequent performance on the somatic signal detection task (SSDT). In Experiment 1, 37 participants completed the SSDT under usual testing conditions and after performing an interoceptive heartbeat perception task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Heartbeat detection accuracy using the formula described above revealed very high overall accuracy in the group (mean value = 0.92, range 0.82–0.97). However, as explained, given that heartbeat ratings used multiple choice responses, these values would be expected to be higher than those found in other studies where subjects reported the number of heartbeats without options from which to choose [Dunn et al, ; Fustos et al, ; Garfinkel et al, ; Herbert et al, ; Mirams et al, ; Pollatos et al, ; Werner et al, ]. Accordingly, the error analysis painted a slightly different picture, revealing a high overall percentage of errors (mean = 76.03%, range 41.67–100%).…”
Section: Resultsmentioning
confidence: 84%
“…Heartbeat detection accuracy using the formula described above revealed very high overall accuracy in the group (mean value = 0.92, range 0.82–0.97). However, as explained, given that heartbeat ratings used multiple choice responses, these values would be expected to be higher than those found in other studies where subjects reported the number of heartbeats without options from which to choose [Dunn et al, ; Fustos et al, ; Garfinkel et al, ; Herbert et al, ; Mirams et al, ; Pollatos et al, ; Werner et al, ]. Accordingly, the error analysis painted a slightly different picture, revealing a high overall percentage of errors (mean = 76.03%, range 41.67–100%).…”
Section: Resultsmentioning
confidence: 84%
“…As to the first question, direct manipulations of attention to the body and studies assessing body awareness generally show that attention focused on the body enhances the sensitivity to interoceptive stimulation and increases symptom reports. This has been documented by studies on tactile stimulation (Mirams et al, 2012), respiration (Stegen et al, 2001), pain (Villemure andBushnell, 2009), itch (Van Laarhoven et al, 2010), dyspnea (von Leupoldt et al, 2007), and general symptom reporting (Verkuil et al, 2007). Interestingly, not just symptom reports but also objective cough frequency is enhanced by focusing attention on internal sensations ( Van den Bergh et al, 2012).…”
Section: Perception and Attentionmentioning
confidence: 78%
“…In a study applying low-intensity tactile stimuli, it was shown that a more liberal response criterion was used when attention was directed inward, leading to more false positives (Mirams et al, 2012). Some groups, such as persons with high-trait negative affectivity (NA) who tend to focus attention inward during a physiological challenge (Stegen et al, 2001), report more symptoms, which are less closely related to the induced physiological changes ( Van den Bergh et al, 2004;Bogaerts et al, 2005).…”
Section: Perception and Attentionmentioning
confidence: 98%
“…The drawing representing participants' right hands has been reversed so that it could be integrated into the frequency maps. 2005; Mirams et al 2012;Bauer et al 2014aBauer et al , 2014b: the perception depends on the representation of the body per se and, therefore, if responses are distorted, then the body representation is distorted (Longo et al 2010).…”
Section: Discussionmentioning
confidence: 99%